Effects of Crotalaria spectabilis extract in Meloidogyne javanica and Heterodera glycines soybean nematodes - Scupinari, Tamires; Mannochio-Russo, Helena [UNESP]; Marcheafave, Gustavo Galo; da Silva Bolzani, Vanderlan [UNESP]; de Oliveira Nunes, Estela; Dias, Waldir Pereira; Hoffmann-Campo, Clara Beatriz; Zeraik, Maria Luiza (Springer Nature, 2024)
Nematodes are a common soybean threat, and the search for new solutions for controlling them has been the focus of many studies worldwide. Crotalaria spp. are known sources of pyrrolizidine alkaloids with nematicidal activities. In this study, the nematicidal and nematostatic effects of C. spectabilis extracts were evaluated in vitro over two different nematode species (Heterodera glycines and Meloidogyne javanica). A full factorial experimental design was employed to understand the effects and interactions of input factors (plant organ, extraction solvent, and nematode species) on the output response (nematode mortality). Ethanolic and alkaline extracts of leaves and seeds were tested at concentrations of 5, 10 and 20 mg L-1 in bioassays with 48 hours of incubation. The C. spectabilis seed’s alkaline extract assessed for H. glycines resulted in higher mortality rates (close to 96%) compared to the other experiments. Therefore, this combination was also evaluated in vivo in a soybean plantation, resulting in a decrease of about 90% in the nematode multiplication factor compared to the control group. Ultra-High Performance Liquid Chromatography coupled to a tandem High-Resolution Mass Spectrometer (UHPLC-HRMS/MS) analyses revealed pyrrolizidine alkaloids in the extract, such as senecionine N-oxide, besides monocrotaline and its derivatives. The results obtained in this study allow new possibilities to handle nematode infections. The direct application of C. spectabilis extracts or their isolated bioactive compounds on soil can be a promising approach.
Keywords: Botanical pesticide; Cover crop; Nematode control; Pyrrolizidine alkaloid; Soybean